2006
DOI: 10.1111/j.1460-9568.2006.04957.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate enhances proliferation and neurogenesis in human neural progenitor cell cultures derived from the fetal cortex

Abstract: Excitatory amino acids such as glutamate play important roles in the central nervous system. We previously demonstrated that a neurosteroid, dehydroepiandrosterone (DHEA), has powerful effects on the cell proliferation of human neural progenitor cells (hNPC) derived from the fetal cortex, and this effect is modulated through NMDA receptor signaling. Here, we show that glutamate can significantly increase the proliferation rates of hNPC. The increased proliferation could be blocked by specific NMDA receptor ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 45 publications
6
92
0
1
Order By: Relevance
“…NMDA at high concentrations can be cytotoxic, depending on receptor density and subunit composition [27]. NMDA could also increase cell proliferation and/or survival, as demonstrated by several groups by in vivo and in vitro experiments [28,29]. …”
Section: Resultsmentioning
confidence: 99%
“…NMDA at high concentrations can be cytotoxic, depending on receptor density and subunit composition [27]. NMDA could also increase cell proliferation and/or survival, as demonstrated by several groups by in vivo and in vitro experiments [28,29]. …”
Section: Resultsmentioning
confidence: 99%
“…Many reports have said that the NMDA receptor has an important role in the proliferation of neuronal progenitors. Glutamate stimulation via NMDA receptors significantly increased the proliferation of human neural progenitor cells derived from the fetal frontal cortex (Suzuki et al, 2006). Neurospheres derived from the embryonic rat brain express the NR1 and NR2B subunits of the NMDA receptor and show reductions in diameter and number (Mochizuki et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, glutamate may have dichotomous effects on neurogenesis, depending on its concentrations. Low concentrations of exogenous glutamate (10 mM) introduced to cell or slice culture led to increased NPC proliferation and neurogenic potentials [19][20][21], whereas high concentrations of exogenous glutamate (300 mM) introduction resulted in impaired DNA synthesis and reduced cellular proliferation [25]. Second, glutamate has a direct neurotoxic effect on mature neurons [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…The product of glutaminase-catalyzed reaction is glutamate, a classical and the most abundantly used excitatory neurotransmitter. Glutamate has long been implicated in the maturation of neurons [18][19][20][21]. Specifically, an in vitro study on NPCs has revealed the role of glutamate in neuronal differentiation through the activation of AMPA receptors [20].…”
Section: Introductionmentioning
confidence: 99%